2020
DOI: 10.1159/000508733
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intraplaque Hemorrhage Is Associated with Cardiovascular Risk Factors

Abstract: Introduction: Intraplaque hemorrhage (IPH) is a known predictor of symptomatic cervical carotid artery disease. However, the association between IPH and modifiable cardiovascular risk factors, patient demographics, and pertinent laboratory values has not been extensively studied. Methods: A retrospective review was performed of consecutive patients who have undergone dedicated carotid plaque imaging over a 3-year period. Patients were excluded if the MR examination did not include high-resolution carotid plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…A previous study found that IPH in carotid plaques using MPRAGE imaging was associated with age, sex, degree of stenosis, and hyperlipidemia [ 35 ], which was, not observed in our study. This may be related to the cohort characteristics where patients with primarily moderate to severe arterial stenosis were included; some also had partial occlusions.…”
Section: Discussioncontrasting
confidence: 87%
“…A previous study found that IPH in carotid plaques using MPRAGE imaging was associated with age, sex, degree of stenosis, and hyperlipidemia [ 35 ], which was, not observed in our study. This may be related to the cohort characteristics where patients with primarily moderate to severe arterial stenosis were included; some also had partial occlusions.…”
Section: Discussioncontrasting
confidence: 87%
“…If the IPH occurs, the treatment approach of the patient is significantly altered [ 16 , 17 ]. Previous studies have tried to differentiate carotid plaques with IPH and those without IPH by using stenosis [ 18 ]. Several studies found that plaques with IPH in the carotid artery showed greater stenosis than those without IPH [ 15 , 18 ], which are consistent with our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have tried to differentiate carotid plaques with IPH and those without IPH by using stenosis [ 18 ]. Several studies found that plaques with IPH in the carotid artery showed greater stenosis than those without IPH [ 15 , 18 ], which are consistent with our studies. The reason may be that the stenosis of the lumen affected hemodynamic parameters, which in turn affected the status of intraplaque neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the risk factors for the presence of IPH and found that that increasing patient's age, male sex, taking an antiplatelet agent, increase in degree of stenosis, or elevated lipids were the risk factors (10,19,23,24). Of these risk factors, in this study, taking an antiplatelet agent and larger baseline carotid plaque-containing vessel wall volume (a related parameter to increasing degree of stenosis) were also found to be associated with plaques in the progressed IPH group.…”
Section: Discussionmentioning
confidence: 99%